THE IMPLEMENTATION OF PARTICIPATORY ERGONOMICS PROGRAM IN THE EFFORTS TO IMPROVE CONCERN TOWARDS WORKPLACE ACCIDENTS (CASE STUDY OF SHOE INDUSTRY) - Sukapto, Paulus; D, Harjoto; Yumanto, Yumanto; Marbun, Romy (Teknologi Indonesia, 2016)
Participatory ergonomics (PE) is an effective and efficient method to improve the employees concern towards workplace accidents in order to work more productively. The success of PE is determined by participation, organization, ergonomic methods and tools, as well as job design concept. The implementation of this method was conducted in the Upper Production Department (the division producing the top part of shoes) which consists of seven work stations. Each work station is measured concerning its risk score (RS). The measurement result shows that Dering and Pouching Stations have RS of more than the determined limit, therefore they need an improvement. The improvement results are protector for Pouching Machine and material clamp for Dering Machine.